2012
DOI: 10.1007/s00425-012-1813-9
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism implicating plastoglobules in thylakoid disassembly during senescence and nitrogen starvation

Abstract: Plastoglobules are lipid droplets present in all plastid types. In chloroplasts, they are connected to the thylakoid membrane by the outer lipid half-bilayer. The plastoglobule core is composed of neutral lipids most prominently the prenylquinones, triacylglycerols, fatty acid phytyl esters but likely also unknown compounds. During stress and various developmental stages such as senescence, plastoglobule size and number increase due to the accumulation of lipids. However, their role is not limited to lipid sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 76 publications
1
33
0
1
Order By: Relevance
“…This was one of the first indications that PG function not only in the storage but also partici-pate in the metabolism of tocopherol [15,20] (Figure 2). The vte1 mutant lacking TC and the vte2 mutant lacking the homogentisate phytyl transferase are both devoid of a-tocopherol.…”
Section: Vitamin K 1 In the Thylakoids And Plastoglobulesmentioning
confidence: 76%
See 2 more Smart Citations
“…This was one of the first indications that PG function not only in the storage but also partici-pate in the metabolism of tocopherol [15,20] (Figure 2). The vte1 mutant lacking TC and the vte2 mutant lacking the homogentisate phytyl transferase are both devoid of a-tocopherol.…”
Section: Vitamin K 1 In the Thylakoids And Plastoglobulesmentioning
confidence: 76%
“…Tocopherol de novo synthesis: the benzoquinone head group is derived from the shikimate pathway and the phytyl tail from the plastidic 1-deoxy-D-xylulose-5-phosphate isoprenoid pathway. Phytyl-DP prenylation by homogentisate phytyltransferase (HPT/VTE2) converts HGA into MPBQ [20,21 ]. TC/VTE1 catalyzes chromanol ring formation in MPBQ leading to the formation of d-tocopherol.…”
Section: Vitamin K 1 In the Thylakoids And Plastoglobulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that chloroplast PGs are dynamic monolayer particles with specialized metabolite and protein content that play an active role in thylakoid formation, remodeling, and breakdown, rather than merely serving a passive storage function as long believed (reviewed in Bréhélin et al, 2007;Besagni and Kessler, 2013). The PG-localized ABC1K family likely plays a regulatory role in PG function, in particular through control of prenyl-lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation for determining the proteomes of lipid droplets, particularly in microalgae, is the purity and the homogeneity of the preparation. Green microalgae, for example, may contain three distinct pools of lipid droplets in one cell: the cytoplasmatic lipid droplets (CLD), the major neutral lipid pool, which are induced under stress conditions such as nitrogen limitation or at the stationary growth phase (Wang et al, 2009); plastoglobules, which are smaller lipid droplets within the chloroplast that have been shown to change in size and number under stress conditions and seem to be involved in stress resistance, metabolite transport, and the regulation of photosynthetic electron transport (Bréhélin et al, 2007;Besagni and Kessler, 2013); and the eyespot structure, part of the visual system in green algae, composed of one or several layers of lipid droplets, characterized by their orange color resulting from a high content of b-carotene (Kreimer, 2009). Disruption of microalgal cells, which is required for the isolation of the lipid droplets, usually involves harsh treatments such as sonication, mixing with glass beads, or use of a French press that breaks not only the cell membrane but also the chloroplast.…”
mentioning
confidence: 99%